Kajian Ruwatan Murwakala Cirebon - Mochamad Reyhan Fauzi; Asep Miftahul Falah; Agus Cahyana (Jurusan Seni Rupa ISBI Bandung, 2025)
This study aims to find out about the art and culture of Ruwatan Murwakala in Cirebon, as we know that in Indonesia there are many traditional customs and ceremonies from various tribes that teach and convey the teachings of goodness so that humans within the scope of the tribe are reflected in how behavior or norms and rules that they have to follow, because customs in Indonesia are always tied to religious teachings or good teachings from their ancestors, Ruwat itself is one of the traditions from Indonesia which is very close to Javanese society where the spread of this tradition has several meanings in Each region has different presentations. If in the Dieng plains ruwatan is a tradition of shaving a child’s hair but it is different from that in Cirebon, ruwatan is a tradition of presenting shadow puppet performances with Cirebon wayang gagrak, which must perform a special play, namely the play about the birth of Batara. Kala. The shadow puppet show is very full of meaning and the teachings of the Tareqat Syathariyah which is very popular among the people of Cirebon, this is what makes the concept of this ruwatan full of meaning from Islamic teachings through the prayers offered by the puppeteer during the performance using the Free language and Arabic. In this study we will also find out the philological aspects of Ruwatan Murwakala Cirebon. By taking a qualitative, descriptive approach.